2022
DOI: 10.3390/sym14102147
|View full text |Cite
|
Sign up to set email alerts
|

On Neighborhood Inverse Sum Indeg Energy of Molecular Graphs

Abstract: The spectral graph theory explores connections between combinatorial features of graphs and algebraic properties of associated matrices. The neighborhood inverse sum indeg (NI) index was recently proposed and explored to be a significant molecular descriptor. Our aim is to investigate the NI index from a spectral standpoint, for which a suitable matrix is proposed. The matrix is symmetric since it is generated from the edge connection information of undirected graphs. A novel graph energy is introduced based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…Notably, we have observed that the energy associated with most degree-based topological indices exhibits a higher correlation coefcient than calculation-based topological indices and is more signifcant. Compared to the literature [46,47], where the topological indices have a higher correlation coefcient, our results are more interesting. Furthermore, our study has mathematically determined the upper and lower bounds of the topological indices, enabling their application to any chemical structure.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Notably, we have observed that the energy associated with most degree-based topological indices exhibits a higher correlation coefcient than calculation-based topological indices and is more signifcant. Compared to the literature [46,47], where the topological indices have a higher correlation coefcient, our results are more interesting. Furthermore, our study has mathematically determined the upper and lower bounds of the topological indices, enabling their application to any chemical structure.…”
Section: Discussioncontrasting
confidence: 47%
“…However, it appears that most of these novel energies have been introduced without considering their specifc utility in chemistry or other relevant felds. Tis study, in contrast, follows a more deliberate approach, drawing inspiration from a previous study [46] that introduces a suitably constructed matrix to generate a novel graph energy based on the eigenvalues of the neighborhood inverse (NI) sum index. Te NI index demonstrates predictive potential and can efectively discriminate between isomers, making it a valuable molecular structural descriptor.…”
Section: Introductionmentioning
confidence: 99%
“…For results related to neighborhood sum-degree-based indices, refer to [17,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The Schultz, Modified Schultz polynomials and their topological indices of Jahangir graphs are obtained in [38]. Recently, Ullah et al, obtained some interesting results on structural characterizations of graphs through degree based topological indices [39][40][41][42][43] and Mondal et al, studied the molecular graphs in [44][45][46][47]. On the other hand, some other properties of topological indices are discussed by Ahmad et al, [48][49][50][51] and Zaman et al, in [52][53][54][55][56][57][58][59].…”
mentioning
confidence: 99%